Power distance in the correspondence between lecturers and students in Australia and Vietnam = khoảng cách quyền lực trong trao đổi thư từ giữa giảng viên và sinh viên tại Úc và Việt Nam. M.A. Thesis Linguistics: 60220201 - Nguyễn, Thành Trung (H.: University of Languages and International Studies, 2018)
71 tr.